2010
DOI: 10.1016/j.ajog.2010.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge of obesity's effects in the pre- and periconceptional periods and avenues for future research

Abstract: The prevalence of obesity is growing among reproductive age women. This is concerning as obesity has significant health related consequences. Aside from long term risks of diabetes, heart disease, and some types of cancer, obesity poses immediate threats for young women including subfertility and adverse early and late pregnancy outcomes. Epidemiologic and experimental studies demonstrate associations between pre-pregnancy obesity and poor reproductive outcomes, however, the mechanisms involved are poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 77 publications
(92 reference statements)
1
115
0
2
Order By: Relevance
“…[52][53][54][55] Perhaps most relevant to our study is the association with fetal growth restriction. 19,56 In addition, obesity is linked to chronic illnesses 57,58 and social disadvantage, 59 which might affect the mother-infant interaction and the resources available to enhance the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] Perhaps most relevant to our study is the association with fetal growth restriction. 19,56 In addition, obesity is linked to chronic illnesses 57,58 and social disadvantage, 59 which might affect the mother-infant interaction and the resources available to enhance the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of obesity on the preovulatory LH surge can be particularly complicated in women with PCOS who frequently have LH hypersecretion and anovulation [5][6][7]. Treatment with insulin sensitizing drugs such as rosiglitizone, a peroxisome proliferator-activated receptor-γ (PPARγ) agonist, may improve ovulation.…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 99%
“…Obese women are almost three times more likely than non-obese women to have some degree of infertility and may take longer to conceive, even if cycling regularly [3,4]. Studies have shown that obese women who do become pregnant have an increased risk of miscarriage, preeclampsia, gestational diabetes, and congenital defects in offspring [5]. In addition to obesity alone, polycystic ovarian syndrome (PCOS) is a common metabolic disorder in reproductive-aged women commonly associated with luteinizing hormone (LH) hypersecretion, hyperandrogenism, insulin resistance, and anovulation [5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Исследования женщин, вступающих в программы ВРТ, показали, что пациенткам с избыточной массой тела и ожирением требуется большая доза гонадотро-пинов и увеличение продолжительности стимуляции суперовуляции для получения такого же количества ооцитов, как у пациенток с нормальным весом [28]. Причиной этого может быть нарушение фармакодина-мики препаратов.…”
Section: ожирение как предиктор неудач в программах вспомогательных рunclassified